Evaluation of the Effects of Topical Ellagic Acid and Graft Application on Bone Regeneration: an Experimental Study - Gul, Mehmet; Dundar, Serkan; Yigin, Akin; Artas, Gokhan; Tanik, Abdulsamet; Bingul, Muhammet Bahattin; Habek, Osman (Uab Stilus Optimus, 2022)
Objectives: The aim of this experimental animal study is to investigate the effect of bone graft and topical ellagic acid application on bone regeneration in rats with critical-sized calvarial bone defects. Material and Methods: A total of 24 male Wistar rats were divided into three groups, and 7 mm critical-sized calvarial bone defects were created surgically in them. In the first group, the created defect was left empty, and this acted as a control group. In the second group, only a bone graft was placed in the created defect. In the third group, in addition to placing a bone graft in the created defect, 0.325 mg/kg ellagic acid (EA) was applied topically to the defect. Results: As a result of semiquantitative scoring, osteoblast counts were 2 (SD 0.82) in the control group, 2.71 (SD 0.76) in the graft group, and 1.14 (SD 0.69) in the EA + graft group. The number of osteocytes was 2.29 (SD 0.76) in the control group, 2.71 (SD 1.11) in the graft group, and 1.43 (SD 0.54) in the EA + graft group. When inflammations were evaluated, values of 1.71 (SD 0.75), 1.14 (SD 0.69), and 3 (SD 0.82) were obtained in the control, graft, and EA + graft groups, respectively. Conclusions: Topical ellagic and graft applications show different effects at different doses under topical and systemic conditions. The dose amount of ellagic acid applied, especially in topical applications, has critical importance in bone healing.
Keywords: bone; ellagic acid; fracture healing; graft